Oxygen Delivery as a Limiting Factor in Modelling Dicopper(II) Oxidase Reactivity. Issue 29 (6th March 2017) - Gülzow, Jana; Hörner, Gerald; Strauch, Peter; Stritt, Anika; Irran, Elisabeth; Grohmann, Andreas
Abstract: Invited for the cover of this issue is the group of Gerald Hörner and Andreas Grohmann at the Technical University of Berlin. The image depicts that the browning of cut fruit is effected by copper‐ and oxygen‐dependent oxygenases, leading to melanine pigments, which are polymeric ortho ‐quinone derivatives. Read the full text of the article at10.1002/chem.201605868 . Abstract : " Attempts to mimic metalloenzymes teach us about catalysis, and the lessons learnt find widespread application in a number of chemical disciplines, including process engineering ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 7009 ff. (DOI:10.1002/chem.201605868 ).